A study of the consumer’s acceptance of two promising strains of bean in Nicaragua. - Munguía, Roberto (2016)
In January, 1994, we performed this research with more than 100 housekeepers in three departments in the Nicaraguan South, with the objective of getting to know the advantages for commerce and for direct consumption of the strains CIA93-B and CNIGB-93, which are currently in their validation stage in the fields. The strain COMPANIA 93-B bested CNIGB-93 in such characteristics as: grain size, shape, shine, color uniformity, grain uniformity and consistency, but was not any better if compared with the variety known as “creole” (known in the region also as “Cuarenteno”), utilized as the comparison sample. By consulting the surveys with those characteristics considered attractive for the commerce, concerning the material to be evaluated, the creole variety surpasses COMPANIA 93-B and, in the last place, we had the variety CNIGB-93. In cooking time and on the characteristics of the soup, COMPANIA 93-B is in the first place, surpassing the sample variety and the CNIGB-93, as wells in the after-cooked characteristics, where again COMPANIA 93-B surpassed the creole and the CNIGB-93.